Konservasi Bahan Pustaka Melalui Penjilidan di Perpustakaan UPT Proklamator Bung Hatta Bukittinggi - Harida, Rezki Putri; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this research are:Â  (1) to describe binding one of library material conservation activities Perpustakaan UPT Proklamator Bung Hatta Bukittinggi, (2) to describe the obstacles faced in the binding activities, (3) to describe how to overcome the obstacles. Data was analyzed deseriptively. Based on data analysis results, can be summarized as follows. First, the Central Library Bung Hatta Proklamator Bukittinggi do with glue and stitch binding books buttocks. Libraries do not press on the book and do not butt cuts with sawing book to enter the pores of glue on the book. Second, the constraints faced in doing bindery are: (1) not complete facilities and equipment to do the binding, so it is not perfect bound books, (2) lack of concern for the preservation and maintenance book, and (3) lack of experts in the bindery. Third, how to overcome obstacles faced in conservation activities through binding library materials are (1) reduce the air humidity, (2) avoid the presence of dust, dirt, oil or other organic matter on paper, (3) prohibit visitors and staff eat, drink or smoking in the library reading room, this could damage library materials collection, (4), should be treated library materials carefully when reading, open and close the book, and (5) try to have an indirect placement library materials due to sunlight. Keywords: deseristively; describe; library material; conservation Â  Â